Advances in novel molecular targets for antidepressants - Wang, Qingzhong (Prog Neuropsychopharmacol Biol Psychiatry, 2020)
Depression is the most common psychiatric illness affecting numerous people world-wide. The currently available antidepressant treatment presents low response and remission rates. Thus, new effective antidepressants need to be developed or discovered. Aiming to give an overview of novel possible antidepressant drug targets, we summarized the molecular targets of antidepressants and the underlying neurobiology of depression. We have also addressed the multidimensional perspectives on the progress in the psychopharmacological treatment of depression and on the new potential approaches with effective drug discovery.